Chemical Characterization, Antioxidant and Enzyme‐Inhibitory Activities of Different Extracts from Three Phlomis Species - Sakina Yagi; Gokhan Zengin; Mehmet Veysi Cetiz; Zoltán Cziáky; József Jeko; Muammer Bahşi; Uğur Çakılcıoğlu; Halbay Turumtay; Abdurrahman Aktumsek (ChemistryOpen)
Phlomis species (family Lamiaceae) are highly valued as food and herbal medicine. The present study is designed to investigate the chemical composition and antioxidant and enzyme inhibitory activities of extracts from P. fruticosa, P. herba‐venti, and P. kurdica aerial parts. Different classes of metabolites, including phenolic acids, phenylethanoids, flavonoids, iridoids, organic acids, terpenes, and fatty acids, are identified in the three species, with methanol as the best solvent to recover bioactive compounds from the three species in addition to ethyl acetate for P. kurdica. Around 70% methanol extract of P. herba‐venti exerts the best radical scavenging and ions‐reducing properties, while its methanol extract exhibits the highest acetylcholinesterase inhibitory activity. The ethyl acetate extract of P. fruticosa displays the best chelating power, and its other polar extracts have the highest total antioxidant activity. Furthermore, molecular docking and molecular dynamics simulations have underscored the therapeutic potential of bioactive compounds, including isoverbascoside, samioside, forsythoside B, and hattushoside. In conclusion, the study indicates that these three Phlomis species are a rich source of bioactive molecules with possible therapeutic applications, and the selection of appropriate extraction solvents is crucial for the targeted biological activity.